Investigation into the reduction of aerodynamic drag via external windshields on high-speed trains - Jin Yongrong; Chen Xiaoli (Journal of Engineering and Applied Science)
Abstract As train speeds increase, aerodynamic drag becomes a significant factor in train resistance. The geometric profile of the train’s end connection changes abruptly, enhancing this aerodynamic resistance. Implementing an external windshield effectively mitigates this resistance, particularly for middle- and rear-train cars. This study utilizes three-dimensional, steady Navier–Stokes (N-S) equations for open line conditions and three-dimensional, unsteady N-S equations for tunnel environments to analyze the drag reduction effects of trains with and without external windshields in both scenarios. The findings indicate that external windshields have minimal impact on the flow and pressure fields surrounding the entire train, whether operating on open lines or in tunnels. However, the installation of an external windshield creates a positive pressure zone on its surface, with varying pressure levels depending on whether the train is in open air or a tunnel. Additionally, a high-velocity airflow occurs in the gap between the external and internal windshields, reaching speeds up to 90 m/s. In open-line conditions, the external windshield decreases the train’s overall aerodynamic resistance by approximately 14.46%, while in tunnels, it achieves a reduction of about 24.48%. Furthermore, the pressure surrounding the windshield is higher during tunnel operations compared to open-line conditions.